Social Criticism in Tekotok’s Hones Translator Corruptor Animation - Sujiati Lestari; Hendra Alfani; Dian Novitasari (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2022)
Various criticisms toward corruptions in Indonesia, especially during the Covid-19 pandemic were conveyed by the public through social media, one of which was social criticism through the Tekotok’s animation on YouTube. This study aims to uncover the meaning behind the sign and how social criticism is depicted in the animation of the Tekotok’s Hones Translator Corruptor. This study uses a critical paradigm approach and used Roland Barthes’ Semiotics as a theory to uncover the meaning in the animation and discover myths. The research shows that Tekotok’s Hones Translator Corruptor displays social criticism that often occurs in real life, such as satire about the corruptor’s behavior, corruption and power relationship, and the lack of punishment for perpetrators of corruption. The myth found in the Tekotok animation is that the first actor who acts feels like a victim to be released from prosecution. The second asks questions about people in lower positions.